Seasonal variation, treatment outcome, and its associated factors among the snakebite patients in Somali region, Ethiopia - Abdullahi, Ahmed; Yusuf, Nejib; Debella, Adera; Eyeberu, Addis; Deressa, Alemayehu; Bekele, Habtamu; Ketema, Indeshaw; Abdulahi, Ibsa Mussa; Weldegebreal, Fitsum (Frontiers in Public Health, 2022)
Background Snakebite is a major cause of mortality and morbidity in many areas, particularly in the rural tropics, and is a major public health problem around the world. It also imposes significant economic burdens on snakebite victims due to treatment-related expenses and lost productivity. Objective The purpose of this study was to assess seasonal variation, treatment outcomes, and its associated factors among snakebite in Denan health center in the Somali region, Ethiopia. Method A facility-based cross-sectional study was conducted from 10 to 30 September 2020 in Denan health center, Somali region, Ethiopia. All snakebite cases in Denan health center from 1 September 2015 to 31 August 2020 were included. Data were collected using a pre-tested structured checklist from the patient cards. Data were entered into EpiData version 3.1 and analyzed using SPSS version 22 (IBM SPSS Statistics, 2013). The prevalence was reported by proportion with 95% confidence interval (CI) and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using an adjusted odds ratio with 95% CI. Statistical significance was declared at p-value < 0. 05. Result The overall prevalence of poor outcome of venomous snakebites was 31.4% (95% CI 26.3% 35.4%). Study participants with an age of less than 10 years old (AOR = 2.01; 95% CI 1.39, 4.05), age between 10 and 30 years old (AOR = 2.06; 95% CI 1.39, 9.30), arrival times greater than or equal to 6 hours (AOR = 2.37; 95% CI 1.39, 4.05), and timing of snakebite (AOR = 0.49; 95% CI 0.31–0.87) were factors found to be significantly associated with poor treatment outcome. Conclusion According to this study, about one in every three snakebite patients have a poor outcome. Patients with poor outcomes were those who did not improve as a result of treatment or died as a result of it. Designing appropriate engagement of public health education about snakebite prevention techniques, particularly during entry and exit of rainy seasons and establishment of appropriate case management protocol is strongly recommended, as well as increasing the accessibility or availability of antivenoms will undoubtedly have a significant impact on the reduction of mortality and disability related to that of the snakebites.